+0  
 
0
76
1
avatar+558 

What is recursive rule for the sequence?

SamJones  May 1, 2018
 #1
avatar+867 
+1

Hi SJ

 

We can plug in the values to find the recursive rule.

 

We plug in n = 1.

 

\(a_1=9(-5)^{1-1}=9\)

 

We imediately eliminate b and c.

 

We plug in n = 2

 

\(a_2=9(-5)^{2-1}=-45\)

 

We can see that only d works.

 

That is your final answer,

 

I hope this helped,

 

Gavin

GYanggg  May 1, 2018

8 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.